Paravertebral Mass in a Patient with Hemolytic Anemia: Computed Tomographic Findings - Juliana França Carvalho; Edson Marchiori; Gláucia Zanetti; Claudia Mauro Mano; Branca Sarcinelli-Luz; Flávia Gavinho Vianna; Carla Assed; Isabella Guedes Santos; Alair Augusto S. M. D. Santos; Alberto Domingues Vianna (Case Reports in Medicine)
Extramedullary hematopoiesis is characterized by the presence of hematopoietic tissue outside of the bone marrow and is typically associated with chronic hemolytic anemias. Intrathoracic extramedullary hematopoiesis is a rare and usually asymptomatic condition. The authors report a case of a 57-year-old man with intrathoracic extramedullary hematopoiesis and hereditary spherocytosis. Clinical and laboratory evaluation, together with radiological findings, are described. The diagnosis of the disease was confirmed by tissue biopsy.